2015
DOI: 10.2196/mental.4074
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Perception of Using Text Messages as an Adjunct Therapy for Low-Income, Minority Mothers With Postpartum Depression

Abstract: BackgroundPostpartum depression (PPD) is the most common medical problem among new mothers that can have a negative impact on infant health. Traditional treatments are often difficult for low-income mothers to complete, particularly given the numerous barriers families face.ObjectiveAmong low-income, primarily racial, and ethnic minority mothers with postpartum depression, our aim was to evaluate (1) the feasibility of sending supportive text messages, and (2) the perception of receiving private, supportive te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…Studies of mHealth technology addressing other sensitive issues, such as safer sex, human immunodeficiency virus (HIV) infection prevention, substance abuse, and depression, have demonstrated its utility in reducing feelings of stigma that can occur during face-to-face counselling [39-42]. This resonates with a clinic-based US study that found that not all women who screened positive for IPV using a computer wanted to share their answers with their health care provider [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mHealth technology addressing other sensitive issues, such as safer sex, human immunodeficiency virus (HIV) infection prevention, substance abuse, and depression, have demonstrated its utility in reducing feelings of stigma that can occur during face-to-face counselling [39-42]. This resonates with a clinic-based US study that found that not all women who screened positive for IPV using a computer wanted to share their answers with their health care provider [15].…”
Section: Discussionmentioning
confidence: 99%
“…The search keywords used included a combination of "postnatal depression"; "postpartum depression"; "intervention"; "adherence with treatment", and "delivery of treatment". The search result was restricted to telephone-based [46] and Internet-based interventions [19].…”
Section: Search Methodologymentioning
confidence: 99%
“…Text messaging in weekly intervals was found to be an effective strategy to enhance adherence to antiretroviral therapy and in improving viral load suppression compared with standard care among patients with HIV [22]. Apart from serving as reminders, text messages can encourage healthy behaviors and serve as a form of inexpensive adjunct therapy in various chronic and behavioral disorders [23]. Mothers at risk for postpartum depression, who received supportive therapy and postnatal education via text, were reported to be more equipped to deal with their depression [23].…”
Section: Prior Workmentioning
confidence: 99%
“…Apart from serving as reminders, text messages can encourage healthy behaviors and serve as a form of inexpensive adjunct therapy in various chronic and behavioral disorders [23]. Mothers at risk for postpartum depression, who received supportive therapy and postnatal education via text, were reported to be more equipped to deal with their depression [23]. A recent study on parents of children aged six to twelve years found healthy behavior tips sent through text were more acceptable than through print or e-mail reminders [24].…”
Section: Prior Workmentioning
confidence: 99%